PERANAN BADAN PEMERIKSA KEUANGAN REPUBLIK INDONESIA PERWAKILAN PROVINSI RIAU DALAM PEMBERANTASAN TINDAK PIDANA KORUPSI BERDASARKAN UNDANG-UNDANG NOMOR 30 TAHUN 2002 TENTANG KOMISI PEMBERANTASAN KORUPSI JUNCTO UNDANG-UNDANG NOMOR 15 TAHUN 2006 TENTANG BADAN PEMERIKSA KEUANGAN - Ladi Titorlianti Batubatra; Erdianto '; Rahmad Hendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Audit Board of the Republic of Indonesia is a body tasked to examine the management and financial responsibility of the state. In Law No. 30 of 2002 on combating corruption commission says that the audit agencies including agencies eradication of corruption. State Audit Agency has implementers in every province, including in Riau Province. Given the high incidence of corruption in the province of Riau requires the Audit Board of Riau Province as the only external audit agencies of government to eradicate corruption. The problem in this thesis is how the role of the Audit Board of the Republic of Indonesia Representatives of the Province of Riau in combating corruption under Act No. 30 of 2002 on the Corruption Eradication Commission in conjunction with Law Number 15 Year 2006 regarding the Audit Board, what factors poses in combating corruption faced by the State Audit Board Representative Riau province, what efforts made by the Supreme Audit Agency Representative Riau province to overcome the barriers to the eradication of corruption. Having done research using empirical methods / sociological, ie the data sources supported by the primary data and secondary data, and after data is collected, the data were analyzed by means of qualitative and conclusion by deductive way.According to the research the role carried out by the Supreme Audit Agency Representative Riau Province is the role of actual or role that is applied in reality (role performance or role playing), factors that are a barrier is the lack of Audit Board members Representatives Provision Riau and lack of budget, as well as efforts conducted by an auditing firm representative Riau province is asking for additional members and ask for a supplementary budget to the finance Audit Agency center. Advice writer, is expected to all interested parties in order to carry out their role and function properly.Keywords: Role-Audit Agency Representative financially- Riau Province-eradication-corruption